(untitled) (Journal of Educational Sciences, 2019)
The article describes the effectiveness of the use of innovative technology in teaching biological features of the medicinal plant Plantago major L. Today, the higher education system in Kazakhstan is undergoing a new stage of modernization. Curricula and training programs for young professionals are being updated. In turn, they place high demands on the level of professional and pedagogical training of teachers. In this regard, recently the interest of students, undergraduates, teachers, faculties, universities in the study of innovative methods of teaching and educating specialists in higher educational institutions has been significantly increasing. In the study of the science of biology, the first section studied is Botany. Since ancient times, paid special attention to medicinal plants, and to this day, researchers have shown high interest in them. The studied medicinal plant Plantago major L. has a wide range. The method of teaching the results obtained in the study of the medicinal plant Plantago major L. using innovative technology has been tested with the participation of 2nd year students of Al-Farabi Kazakh National University. As a result of the use of innovative methods, students were well aware of the information and an increase in the level of knowledge was determined. The results obtained in the study can be used in the process of learning courses such as "Botany", "Medicinal plants", "Anatomy and morphology of the plant." Key words: innovation, innovative technologies, medicinal plants, Plantago major L., interactive demonstration lecture, vertical laboratory, flexible model, laboratory rotation, internal laboratory.